2019
DOI: 10.1039/c9nr00207c
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-based probes for molecular imaging: from basic research to the bedside

Abstract: Molecular imaging is very important in disease diagnosis and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 93 publications
0
46
0
Order By: Relevance
“…A review written by Xia et al outlines the design of these probes, geared toward clinical applications. 9 …”
Section: Nanocontrast Agentsmentioning
confidence: 99%
“…A review written by Xia et al outlines the design of these probes, geared toward clinical applications. 9 …”
Section: Nanocontrast Agentsmentioning
confidence: 99%
“…All liposomes destined for in vivo studies are often decorated with PEG units in order to limit their uptake by RES and to promote enhanced cellular uptake and accumulation in the target tissue. A review on the lipid compositions of different liposome-based probes utilized for in vivo applications indicated that these were mostly designed with DPPC, cholesterol and DSPE-PEG2k as the main components [ 337 ]. The molar ratio between DPPC and cholesterol in different formulations varied a lot albeit the DSPE-PEG2k ratio remained between 4–6%.…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…The molar ratio between DPPC and cholesterol in different formulations varied a lot albeit the DSPE-PEG2k ratio remained between 4–6%. Notably, the DSPC- and HSPC-based formulations are more stable than DPPC-based ones under in vivo conditions while the EPC- and DOPC-based formulations are less stable due to their lower transition temperatures, respectively [ 337 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…Liposome-based probes are currently under investigation to enhance SPECT and PET imaging in a range of diagnostic settings. For example, PS-containing liposomes of 100 or 200 nm (PS100 and PS200) were injected into Watanabe heritable hyperlipidemic rabbits, scanned with SPECT and compared with CT images 48 h after injection ( Figure 2) [64].…”
Section: Nuclear Imaging (Pet and Spect)mentioning
confidence: 99%